Bullet injury to great vessels of abdomen - a case report and review of literature - Rana, Indrajit; Lukram, Ajit (International Surgery Journal, 2016)
Bullet injury to the great vessels of abdomen is uncommon and has high mortality and morbidity including amputation. Many times there are other associated organ injuries. Though hypotension and absent or feeble peripheral pulse are good indicators of vascular injury, there can be normal blood pressure with palpable pulses initially when there are hematoma formation in a closed space and adequate fluid resuscitation. We report this uncommon presentation in a 26 years old gentleman who had bullet injury in the right lower flank of abdomen causing a longitudinal tear on the medial aspect of right external iliac vein (zone III injury) with multiple small intestinal perforations.